Annual Plan 2011-12 Government of NCT of Delhi - Planning Commission (Planning Commission, 2011)
The Annual Plan 2011-12 is the 5th and last Annual Plan under the 11th Five Year Plan 2007-12. The Government of NCT of Delhi has dedicated the 11th Five Year Plan 2007-12 towards having development with human face and making Delhi a global city. This is on the line of thrust of Planning Commission to have faster and more inclusive growth during 11th Five Year Plan.
Government of NCT of Delhi, Planning Department